Prevalence and Pathogen Distribution of Neonatal Sepsis Among Very-Low-Birth-Weight Infants - Wai Ho Lim; Reyin Lien; Yhu-Chering Huang; Ming-Chou Chiang; Ren-Huei Fu; Shih-Ming Chu; Jen-Fu Hsu; Peng-Hong Yang (Elsevier, 2012)
Neonatal sepsis contributes to great mortality and morbidity among very-low-birth-weight (VLBW) infants. Prevalence and pathogen distribution of sepsis in the neonatal intensive care units (NICUs) vary with time and geographic location. Such information serves as a guide for selection of empirical antibiotics coverage. Methods: This is a case series study performed by retrospective chart review of VLBW infants (birth body weight, BBW, <1500 g) in a medical center during a 5-year period from January 2005 to December 2009. Episodes of positive blood cultures, pathogen distribution and related clinical manifestations were described. Results: A total of 158 episodes of sepsis were identified from 1042 VLBW infants. Sepsis rate was 152 per 1000 live births. The vast majority of infections (60.7%) were caused by Gram-positive organisms [G(+)], and overall Coagulase-negative staphylococci (CoNS) (52.5%) were the most common pathogen identified. Prevalence for early-onset sepsis (EOS) was 1% and for late-onset sepsis (LOS) was 14.2%. Infants with EOS had a much higher case fatality rate than LOS (40% vs. 4.7%). Escherichia coli (40%) were the leading pathogen of EOS while CoNS (54.7%) was the leading pathogens of LOS. Overall, apnea and/or bradycardia and/or cyanosis (65.8%), poor activity (48.7%), and increased respiratory effort (43.0%) were the most common presenting features of sepsis. Conclusion: Unlike term infants, Gram-negative organism and E coli were the leading pathogen of EOS among VLBW infants. Judicious and timely use of antibiotic therapy is crucial in the care of VLBW infants.